Physicochemical properties of sodium alginate edible film incorporated with mulberry (Morus australis) leaf extract - Yan, Ling Kuan; Sivanasvaran, S. Navin; Pui, Liew Phing; Yusof, Yus Aniza; Senphan, Theeraphol (Universiti Putra Malaysia Press, 2020)
In this study, sodium alginate film incorporated with mulberry leaf extract [0-4 % (v/v)] were evaluated in terms of its physicochemical properties. Results showed that with the increase of mulberry leaf extract concentration, the thickness of the film increased (from 0.07 mm to 0.11 mm), while the color of film produced increased in its green and yellow intensity. In terms of mechanical properties, with the increase of mulberry leaf extract concentration, a significant increase in the tensile strength but a significant decrease in the elongation at break of the film were observed, while no significant effect (p>0.05) on the puncture force was observed. Similarly, no significant effect (p>0.05) on moisture content, water solubility, and water activity of sodium alginate films were found, with the increase of mulberry leaf extract. An increase in the total phenolic content from 8.92 mg GAE/100 g to 41.88 mg GAE/100 g was observed when 4 % (v/v) of mulberry leaf extract was added.